2005
DOI: 10.1038/sj.ejcn.1602156
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status following malaria control in a Vietnamese ethnic minority commune

Abstract: Objective: To study whether control of malaria leads to catch-up growth or an increase of obesity in a marginally nourished population. Setting: A Vietnamese ethnic minority commune in southern Vietnam. Design: Repeated annual anthropometric surveys were performed from 1995 to 2000. Z-scores for height, weight and BMI for age and weight-for-height were determined by using NCHS 1978 and CDC 2000 reference tables and by the LMS method. Intervention: Active malaria control that reduced the parasite carrier rate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…vivax malaria experienced delayed linear and weight growth [ 20 ]. Available reports indicating that malaria infection can trigger acute undernutrition [ 36 , 37 ] and the effect of reducing malaria transmission on the improvement of undernutrition among children [ 38 40 ] are in agreement with our findings. We did not find an association for many of the investigated relationships, in particular for children below the age of 5.…”
Section: Discussionsupporting
confidence: 93%
“…vivax malaria experienced delayed linear and weight growth [ 20 ]. Available reports indicating that malaria infection can trigger acute undernutrition [ 36 , 37 ] and the effect of reducing malaria transmission on the improvement of undernutrition among children [ 38 40 ] are in agreement with our findings. We did not find an association for many of the investigated relationships, in particular for children below the age of 5.…”
Section: Discussionsupporting
confidence: 93%
“…Malaria in particular has been well studied as a contributor to child and adult nutritional status, and is endemic on Ambae, but not on Futuna. Multiple studies have demonstrated that malaria is related to deficits in nutritional status in children and adults (Friedman et al 2003;Nyakeriga et al, 2004;Pereira et al, 1995), and that treatment of malaria can lead to improved growth and weight gain in children (Hung et al, 2005). We also observed that stature in adult males was significantly greater on Futuna than on Ambae; adult stature is a reflection of conditions experienced during growth and development, including infection (Cole, 2003).…”
Section: Contributors To Differences In Adult Melanesian and Polynesisupporting
confidence: 52%
“…Some of the clearest evidence for the impact of diseases comes from efforts to reduce their health burden. For example, treatment for the common gastrointestinal infection Helicobacter pylori in Colombian children improved growth (Mera et al, ), while malaria treatment in Vietnam reduced the prevalence of stunting (Hung et al, ). In India, the Universal Immunization Program was associated with greater weight and height in childhood (Anekwe and Kumar, ).…”
Section: Revisiting the Obstetrical Dilemmamentioning
confidence: 99%